2001
DOI: 10.1177/194589240101500503
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Portable Spirometer for Studies on the Nasal Cycle

Abstract: Studies based on the nasal cycle are difficult because multiple measurements of nasal patency need to be made over many hours. There is a great need for a simple portable instrument that can be used away from the clinical laboratory for studies on the nasal cycle. Our aim was to investigate the usefulness of a small portable spirometer in studying the nasal cycle. The Mir Spirobank spirometer was fitted with a nasal adapter to measure the volume of air expired from each nasal passage during a slow vital capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 4 publications
(2 reference statements)
0
25
0
2
Order By: Relevance
“…3 Nasal adapters have also been fitted to spirometers to enable measurement of nasal FEV 1 , nasal forced inspiratory volume in 1 second, and nasal forced vital capacity. 4,5 Peak flow and rhinomanometry represent physiologic measures. Rhinomanometry involves the simultaneous measurement of nasal airflow and the pressure required to achieve that flow, from which nasal airway resistance (NAR) can be calculated.…”
mentioning
confidence: 99%
“…3 Nasal adapters have also been fitted to spirometers to enable measurement of nasal FEV 1 , nasal forced inspiratory volume in 1 second, and nasal forced vital capacity. 4,5 Peak flow and rhinomanometry represent physiologic measures. Rhinomanometry involves the simultaneous measurement of nasal airflow and the pressure required to achieve that flow, from which nasal airway resistance (NAR) can be calculated.…”
mentioning
confidence: 99%
“…8 This measurement method may have considerable advantages for studying the severity of nasal septal deviation, since it is quick, independent, easy to use and does not require complex calculations. 7 This method is purely inspiratory rather than expiratory, and demonstrates reciprocal vital capacity in accordance with the patient's complaints. The percentage of airflow obstruction on the obstructed side, in comparison with the non-obstructed side, is measurable and interpretable.…”
Section: Discussionmentioning
confidence: 95%
“…Recent research has reported that nasal spirometry is accurate, reliable and reproducible. It has been shown that the nasal partitioning of airflow as measured by spirometry was directly comparable with results as measured by the rhinomanometer 11 . Further work has produced a normal reference range for nasal spirometry in 100 healthy asymptomatic individuals 12 …”
mentioning
confidence: 78%
“…Hanif et al 11 first described the use of nasal spirometry as an objective measure of the nasal partitioning of airflow in 2001. The spirometer has the potential to overcome many of the disadvantages of the more conventional objective measurements of the nasal passages such as rhinomanometry.…”
mentioning
confidence: 99%